PP.07.36: TARGET BLOOD PRESSURE LEVELS AT DIFFERENT DOSE COMBINATION LERCANEDIPINE WITH DILTIAZEM IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION. (June 2015) - Rekovets, O.; Sirenko, Y.; Dobrokhod, A.; Torbas, O.; Kushnir, S.; Primak, G.; Vaschylko, A.; Granich, V.; Sidorenko, P.; Polyschuk, S.
Abstract : Objective: The aim was evaluate the target blood pressure at different dose combination lercanedipine with diltiazem in patients with mild to moderate arterial hypertension. Design and method: 67 patients were included (37-men, 30-women). Systolic (SBP) and diastolic (DBP) blood pressure, heart rate, ambulatory blood pressure monitoring (ABMP) and central blood pressure (cBP), pulse wave velocity (PWV), augmentation index (Aix) baseline and 1 month of treatment were evaluated. It was 4 combination: lercanedipine/diltiazem - 20/240 mg (n = 16), 10/240 mg (n = 15), 10/120 mg (n = 19), 20/120 (n = 17) mg daily dose. Mean age of patients was 50, 31 ± 0, 75 yr., BMI - 29, 72 ± 0, 35 m2, initial SBP - 151, 21 ± 1, 23 mmHg, DBP - 92, 78 ± 0, 78 mm Hg., heart rate - 68, 34 ± 1, 22 b.m. Results: In combination lercanedipine 20 mg with diltiazem 240 mg target office blood pressure was 56, 25%, target blood pressure at ABPM was 62, 50% patients. In combination lercanedipine 10 mg with diltiazem 240 mg target office blood pressure was 66, 67%, target blood pressure at ABPM was 73, 34% patients. In combination lercanedipine 10 mg with diltiazem 120 mg target office blood pressure was 52, 63%, target blood pressure at ABPM was 78, 95% patients. In combination lercanedipine 20 mg with diltiazem 120 mg target office blood pressure was 82, 35%, target blood pressure at ABPM was 52, 94% patients. We did not note any negative changes in biochemical and clinical laboratory data. Conclusions: the highest percentage achieving target blood pressure on office was the combination lercanedipine 20 mg with diltiazem 120 mg therapy – 82, 35% but the highest percentage achieving target blood pressure at ABPM was in combination lercanedipine 10 mg with diltiazem 120 mg therapy – 78, 95%.